Boosting Innate Immunity During SARS-CoV-2 Clearance - Mehata, Abhishesh K.; Dehari, Deepa; Mehta, Anuj Kumar; Miya, Alim (Coronaviruses, 2021)
Currently, humanity is suffering from a highly contagious and infectious novel coronavirus disease. Due to the unavailability of any specifically approved therapy to eradicate this pathogenic virus, day by day, it is claiming more and more lives of humans. Observing the current scenario, human civilization seems to be in dangerous situation, and the development of a potential vaccine against this invisible enemy may take some more time. It was observed that the individual immune system plays an important role in the fight against the novel coronavirus. Additionally, the innate immune system of the host acts as the first line of defense against invading pathogenic viruses. The host innate immune cells can detect and detoxify the evading viruses. Thus, boosting the innate immune response via targeting activator or inhibitory immune check points pathways for enhancing T-cell immune response may potentially help the patients to fight against this deadly virus. The aim of this editorial is to discuss in brief about the pathogenesis of COVID-19, the role of innate immunity and autophagy during viral clearance.
Keywords: convalescent plasma therapy